1H NMR-based metabolomics approach to evaluate the effect of Xue-Fu-Zhu-Yu decoction on hyperlipidemia rats induced by high-fat diet - Song, Xingfang; Wang, Junsong; Wang, Pengran; Tian, Na; Yang, Minghua; Kong, Lingyi (Journal of pharmaceutical and biomedical analysis, 2013)
[Display omitted] ► Effect of XFZYD on hyperlipidemia rats were investigated by NMR-based metabolomics. ► Seventeen marker metabolites were indentified to be hyperlipidemia concerned. ► Six isolated pathways were identified to be implicated in hyperlipidemia. ► The anti-hyperlipidemia efficacy of XFZYD was confirmed firstly in a global scale. ► Metabolomics is helpful for understanding of the hyperlipidemia-related mechanisms. An NMR-based metabolomics approach was conducted to holisticly explore the effect of XFZYD (a traditional Chinese medicine formula) on high-fat diet induced hyperlipidemia rats with one of the commonly used antihyperlipidemic agents, simvastatin as the positive control. NMR spectra from blood plasma combined with statistical analysis revealed compounds distinguishing hyperlipidemia rats from normal control rats. XFZYD could ameliorate hyperlipidemia by intervening in some major metabolic pathways, such as decreasing the accumulation of ketone body (β-hydroxybutyrate) and acetyl-glycoproteins, enhancing glutathione (GSH) biosynthesis, partially reversing energy and lipid metabolism disturbance. Oral administration of XFZYD could also be helpful to hyperlipidemia rats in bettering the serum chemistry profile. The combined results demonstrated that XFZYD could ameliorate the hyperlipidemic symptoms in a global scale and restore the abnormal metabolic state to a near normal level in a time-dependent pattern.